The Role Of Information Technology In Enhancing The Effectiveness Of Education Management In Schools - Nur Anisyah; Taufiq Rohman; Sesti Novalina; Putri Rahmi Virani Lubis; Arsanur Rahman; Ariyani, Rika (IJGIE (International Journal of Graduate of Islamic Education), 2025)
The advancement of information technology has had a significant impact on educational management in secondary schools (SMP/MTs). This study aims to analyze the role of information technology in enhancing the effectiveness of educational management, particularly in the aspects of administration and communication. The research employs a library research method, collecting data from various secondary sources such as books, journal articles, research reports, and other relevant documents. The findings indicate that information technology contributes to improving school administrative efficiency through the automation of attendance recording, grade management, and financial administration. Additionally, information technology strengthens communication among teachers, students, parents, and school staff through digital platforms, enhancing collaboration in the educational process. However, this study also identifies challenges in implementing information technology, such as the digital divide, lack of teacher training, and resistance to change. Therefore, strategies are needed to improve infrastructure access, strengthen digital literacy among educators, and establish policies that support the optimal utilization of technology in secondary education. This research provides theoretical insights into the impact of information technology on educational management and can serve as a reference for policymakers and practitioners in developing more effective strategies for implementing information technology, particularly in Islamic education within madrasahs.